Status of Pradhan Mantri Jan Dhan Yojna in Uttarakhand: An Initiative Under Financial Inclusion - Nayyar, Ramanpreet Kaur (Journal of Commerce and Trade, 2017)
The irony of the Indian growth story is that where on one hand, a certain proportion of the population is enjoying the accessibility of banking services; on the other hand, another segment remains underprivileged. The lower income strata are totally deprived of even basic financial services. Though banking industry is growing both horizontally and vertically, in spite that the penetration of branches in rural areas does not match with the rising demand and the need for accessible financial services. Even after decades of Bank nationalization, the country is still struggling for the access of financial services and still a large proportion of the nation depends on money lenders or the informal sector who are continuously exploiting the poor. In this regard, many initiatives have been taken by the government to include the exclusions. PMJDY launched in 2014 is one of such initiative. This paper attempts to put forth the status of Pradhan Mantri Jan Dhan Yojna, an initiative under financial inclusion. JEL Classification : E 52, G 21, G 32.